DeutschGPT – Deutschunterricht im Dialog mit Künstlicher Intelligenz (Literatur – Medien – Didaktik, 2025)
Large generative language models (LLMs) have lost the exoticism of their early days. They have long since become part of everyday life, including in teaching and learning. In this new phase of linguistic and literary didactics dealing with ChatGPT and similar tools, German language education must confront new theoretical and practical questions: How does AI work, and what can we expect from this technology in the future? How does the use of AI affect the acquisition of language skills? How do students interact with digital text generators, and what consequences does this have for their educational development? How can AI be meaningfully integrated into German language teaching? Where do the risks lie, and where are the opportunities for shaping the school of tomorrow? The contributions in this volume explore these and other questions. They also present a selection of current research projects related to the use of AI in German language education. As such, the volume provides a comprehensive overview of the current state of research on the topic of German language teaching and AI.